Organic flexible thermoelectric generators: from modeling, a roadmap towards applications. Issue 1 (19th January 2017) - Beretta, D.; Perego, A.; Lanzani, G.; Caironi, M.
Abstract : Organic thermoelectrics are emerging as strong candidates for micro energy harvesting devices to power low energy electronics and serve as sustainable distributed energy supplies. Here their actual potential is assessed with respect to different applications scenarios, such as wearables and sensors networks, providing useful guidelines for their future development. Abstract : Micro energy harvesting to power low energy electronics has been recognized to be of primary importance for today's society to pursue a sustainable supply of energy by the integration of networks of sensors and actuators into smart grids. In this context, sustainable exploitation of distributed renewable energy sources represents a key aspect. Among the variety of sustainable energy conversion technologies, thermoelectric technology is receiving increasing attention because of its capability to harvest energy at the microscale, in the dark, with no moving parts and thus with limited maintenance. In this framework, organic materials, due to their intrinsic electro-mechanical properties, are studied with the aim to realize flexible, battery competitive and/or complementary, thermoelectric generators, and thus to expand the potential of thermoelectrics to all those applications not viable with the present technology based on rigid architectures. In this work, the strengths and limitations of the organic technology are analyzed, identifying a set of novel and promising applications of flexible thermoelectric generators based on organic matter, clearly outlining minimum thermoelectric property requirements to be achieved and ultimately paving the way towards future applications. The study clearly identifies the closest opportunity in the adoption of organic micro-thermoelectric generators for powering distributed sensors in housing and industrial environments, while evidencing the requirement of advanced generator architectures and/or material thermoelectric property breakthroughs in order to realistically target wearable applications.